Strategi Efektif Manajemen Pengetahuan dalam Sistem Informasi Organisasi Berbasis Teknologi Informasi - Nurman Dwi Sulistyo; M Syukur; Sajida Nur Hasannah; Aries Saifudin (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
Effective knowledge in managing knowledge in information systems of information technology-based organizations is a complex challenge. In the face of rapid change and fierce competition, organizations need to adopt appropriate strategies to optimize the use of knowledge in the context of technology-based information systems. The purpose of this study is to conduct a literature review using qualitative methods in understanding effective knowledge management strategies in information systems of information technology-based organizations. The qualitative literature review method is used to collect, analyze, and synthesize existing relevant research and literature. The results of this literature review reveal that effective knowledge management strategies in information systems of information technology-based organizations involve several key aspects. First, efficient knowledge management involves identifying relevant and strategic knowledge, organizing knowledge, as well as utilizing information technology to facilitate access to and sharing of knowledge across the organization. In addition, the use of appropriate information technology in information systems of information technology-based organizations is also an important element in this strategy. The use of knowledge databases, collaboration platforms, and integrated information systems enables organizations to effectively manage and disseminate knowledge.